The Empowering of Alert Husbands in Maternal's Class to Increasing Knowledge and Skills of Labor Pain Management Techniques: Pemberdayaan Peran Suami Siaga Pada Kelas Ibu Hamil Dalam Meningkatkan Pengetahuan dan Keterampilan Melakukan Teknik Manajemen Nyeri Persalinan - Dwie Yunita Baska; Nispi Yulyana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Maternal Class is one of the essential activities that respectful care for making maternal and safe childbirth. However, in reality, so far these maternal classes have only been attended by mothers themselves, without the participation of husbands as birth attendants, even though since 2000, the Indonesian government has launched the Alert Husband program. Therefore, the community service team in collaboration with the midwife made efforts to empower the participation of husbands in-class activities for pregnant women to increase the knowledge and skills of husbands as facilitators of childbirth assistance, especially in carrying out labor pain management techniques. The main target of this activity is 10 couples of husband and wife, with counseling methods, discussions, simulations, and practical demonstrations. The results of this activity were very satisfying and effective, there a knowledge increase score was obtained with an average of 45.50 to 93.50, and skills from a value of 5.60 increased to 10.00. Furthermore, it is hoped that this maternal's class will be routinely carried out at least once a week so that the Alert husband's role will continue to be active and sustainable.